Interventional effects of mesenchymal stem cells on epithelial–mesenchymal transition in head and neck squamous cell carcinoma and underlying mechanisms: a systematic review and meta-analysis of in vitro studies - Wang, Youhu; Liu, Yanli; Du, Wanxian; Xue, Jing; Ruan, Jianhua; Yu, Juan; Ma, Bin; Li, Xun (Frontiers in Immunology, 2026)
BackgroundMSCs are an important component of the TME and play a key role in tumor progression. Based on existing in vitro studies, this research aims to investigate the role of mesenchymal stem cells in the EMT of HNSCC and its related mechanisms.MethodsAccording to the PRISMA guidelines, we systematically searched PubMed, Embase, and Web of Science databases for relevant in vitro studies up to May 6, 2024. Two trained researchers independently performed literature screening, data extraction, and quality assessment, with cross-checking of results. Any disagreements were resolved through discussion or by consulting a third party. Meta-analysis was conducted using Stata 17 software.ResultsA total of 8 in vitro studies were included, involving OSCC, NPC, and TSCC. The meta-analysis results indicate that MSC intervention may be associated with a reduction in the expression of epithelial markers and an increase in mesenchymal markers and related transcription factors in cancer cells, implying a potential role for MSCs in promoting EMT in vitro. Furthermore, a preliminary review of the underlying molecular mechanisms suggests that this process may involve the potential regulation of multiple signaling pathways, including NF-κB, PI3K/Akt/mTOR, IL-6R/JAK/STAT3, CXCL8/CXCR2, TGF-β/Smad, and FGF19-FGFR4.ConclusionsThe existing in vitro evidence suggests that mesenchymal stem cells may exhibit a potential to promote EMT in HNSCC, potentially regulating tumor progression through multiple signaling pathway networks and providing new potential targets for future therapies targeting the TME. However, more high-quality, standardized in vivo and in vitro studies are needed to further validate the related mechanisms and therapeutic potential.